Differential susceptibility of type 1 and type 4 gonococci to chlorhexidine (Hibitane). Issue 4 (August 1975) - Waitkins, S A; Geary, I
Abstract : Virulent Type 1 gonococci have been shown to be much more suceptible to the killing action of Hibitane gluconate than the avirulent Type 4. Those exploring the possibility of genital prophylaxis as a means of controlling gonorrhoea might find Hibitane worthy of consideration.